Hepatitis B virus outreach to immigrant population in Greater Boston Area: Key to improving hepatitis B knowledge - Raissa Djoufack (2018)
© 2017 The Author(s). Published by Baishideng Publishing Group Inc. All rights reserved. Aim: To characterize the understanding of hepatitis B virus (HBV) and determine if outreach improves HBV understanding among Greater Boston Area immigrants. Methods: Six outreach sessions were held in various community venues in the Greater Boston Area. Verbal consent was obtained from participants prior to starting each session. Each session included a pre-session questionnaire, followed by a teaching session, and then a post-session questionnaire. In person interpreters were present for translation during the teaching session and assistance for questionnaire completion when needed. The questions were developed based on the HBV clinical experience of physicians who serve largely immigrant populations. Questionnaires included Likerttype scale, open-ended, and true-false questions. All results were anonymous. Results: One hundred and one people participated in this study. Participants were 30% male with ages ranging from 19 to 87 years. The study population included immigrants from 21 countries, as well as seven United States-born participants. The greatest numbers of participants were from Somalia (44%), Morocco (10%), and Cameroon (8%). Pre session questionnaires revealed that 42% of participants were unaware that HBV can cause cancer, and 50% were unaware that therapies for HBV exist. Our brief teaching intervention led to improved scores on post session questionnaires. For example, at baseline, 58% of participants responded correctly to the question "HBV infection can cause scarring of the liver and liver cancer", whereas 79% of participants responded correctly after the teaching session (P = 0.01). Furthermore, the mean of total correct answers in the true or false portion of the questionnaire increased from 5.5 to 7.6 (P < 0.001). Conclusion: A teaching session targeting Boston Immigrants atrisk for HBV helped improve scores on HBV knowledge questionnaires. Outreach may empower at-risk patients to pro-actively seek HBV care.